2020
DOI: 10.1186/s42077-020-00069-8
|View full text |Cite
|
Sign up to set email alerts
|

Warm blood cardioplegia versus cold crystalloid cardioplegia for coronary artery bypass grafting (CABG) in patients with low ejection fraction

Abstract: Background Patients with reduced ejection fraction (EF) undergoing CABG are more likely to develop postoperative morbidity and mortality. It is controversial about which cardioplegia solution, temperature, and method of administration ensure optimal cardiac muscle preservation during CABG surgery. Aim of the study The aim of the study was to compare intermittent antegrade warm blood cardioplegia with cold crystalloid cardioplegia during CABG in patients with low EF (30–40%). Methods Patients (n = 100) underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, warm cardioplegia correlated with better postoperative cardiac indices and lower peak creatine kinase MB concentrations than cold cardioplegia [28]. The latter findings, along with reduced postoperative cardiac troponin levels, have been replicated in other studies [29,30]. Meanwhile, other studies comparing warm blood and cold crystalloid hyperkalemic cardioplegia do not show significant differences with respect to perioperative myocardial infarction and low cardiac output syndrome [31].…”
Section: Warm Vs Coldmentioning
confidence: 74%
“…However, warm cardioplegia correlated with better postoperative cardiac indices and lower peak creatine kinase MB concentrations than cold cardioplegia [28]. The latter findings, along with reduced postoperative cardiac troponin levels, have been replicated in other studies [29,30]. Meanwhile, other studies comparing warm blood and cold crystalloid hyperkalemic cardioplegia do not show significant differences with respect to perioperative myocardial infarction and low cardiac output syndrome [31].…”
Section: Warm Vs Coldmentioning
confidence: 74%
“…These results support our study 22 . In a second trial, there was no difference found in the postoperative release of CK-MB in the first 48 hours between the two groups (p=0.86) 19,20,21,22,23 .…”
Section: Discussionmentioning
confidence: 86%
“…Blood cardioplegia at physiological temperature will improve the postoperative outcome for better myocardial protection due to the improvement of oxygen availability. Also, blood will improve the oxygen carrying capacity and is less accompanied with hemodilution 5 . Although cold cardioplegia can lower myocardial oxygen consumption and demands, myocardial enzymes may inhibit and delay metabolic and functional cardiac recovery after surgery.…”
Section: Introductionmentioning
confidence: 99%